The Relationship Between Quality of work life and Organizational Commitment of Government Staff. A Case Study: The Department Sector in Luang Prabang Province - Duangvilaykeo, Thipphavanh; Indavong, Dalounny; Sifongxay, sangthong; Khomthavong, Phonepasith; Bounkeomany, Paphaychit (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
At present, for any organization to achieve success according to its goals and objectives, it must rely on many important factors. In particular, human resources are considered a key factor that enables the organization to operate efficiently. They also serve as a vital driving force for the organization’s development and for moving forward toward its established goals. This study aims to: 1) investigate the level of quality of work life among civil servants in the provincial departments of Luang Prabang Province; 2) assess the level of organizational commitment among these civil servants; and 3) examine the relationship between quality of work life factors and organizational commitment within this population. The sample comprised 384 civil servants employed across various provincial departments in Luang Prabang Province. Data were collected using a structured questionnaire, with responses measured on a 5-point rating scale. Statistical analyses employed in this study included frequency, percentage, mean (), standard deviation (SD), and Pearson's correlation coefficient (r) to determine the relationships between variables. The findings of the study revealed the following: 1) The overall quality of work life among the civil servants was found to be at a high level (Mean = 3.73, SD = 0.53). 2) The overall level of organizational commitment among the civil servants was also determined to be high (Mean = 3.80, SD = 0.48). 3) A moderate correlation (r = 0.41 – 0.60) was observed between organizational commitment and the following quality of work life factors: fair and adequate compensation, a safe and health-promoting work environment, and work-life balance. Furthermore, a strong correlation (r = 0.61 – 0.80) was identified between organizational commitment and factors such as employee capacity building, career advancement and professional development, teamwork and interpersonal relations, personal rights and workplace democracy, and the social relevance of the work.